DEVELOPMENT OF A MODERATE ISLAMIC RELIGIOUS EDUCATION CURRICULUM: CHALLENGES AND STRATEGIES IN SCHOOLS AND MADRASSAS - Erliyana Erliyana; Agus Pahrudin; Agus Jatmiko; Koderi Koderi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This study discusses the development of the Islamic Religious Education (IRE) curriculum, grounded in religious moderation, to shape wasathiyah Muslim students who are tolerant, fair, and have a strong sense of national identity. Using a qualitative approach with library research methods, this study analyses various literature and educational policies related to moderate Islamic education. The findings reveal that the core values of moderation tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and i'tidal (justice) form the foundation of a moderate IRE curriculum. However, its implementation still faces challenges, including limited teacher understanding, a lack of professionalism, low digital literacy, and weak institutional support. Recommended strategies include integrating moderation values into the curriculum, enhancing teacher competence, applying contextual and digital-based learning methods, and strengthening inclusive school culture. The study contributes to the development of Islamic education that is contextual, moderate, and aligned with the spirit of rahmatan lil 'alamin.